Effects of ciprofloxacin on bacterial abundance and enrichments in samples taken from the sea surface microlayer and underlying waters in the southern North Sea - Adenaya, Adenike; Zumbika, Florence; Rios-Quintero, Ruben; Lara-Martín, Pablo A.; Wurl, Oliver; Könneke, Martin; Ribas-Ribas, Mariana; Hamprecht, Axel; Brinkhoff, Thorsten (Frontiers in Microbiology, 2025)
The sea surface microlayer (SML), a biofilm-like environment, is a unique and challenging habitat for microbes, due to its position at the interface between the ocean and the atmosphere. In coastal areas, microbial communities in the SML are often exposed to anthropogenic pollutants, including heavy metals, microplastics, and pharmaceuticals. While studies have been conducted on the effects of some of these pollutants, further research is needed to understand the impact of antibiotics on the development of bacterial resistance in the SML. Ciprofloxacin showed high effectiveness against SML bacteria in a previous study. Thus, we investigated the effects of different concentrations of this antibiotic on the dynamics of bacterial communities in samples of the SML and the corresponding underlying water (ULW) over time. Ciprofloxacin concentrations of 50 and 100 ng/mL affected bacterial cell numbers and exerted selective pressure on bacterial communities. A non-metric multidimensional scaling (dissimilarity matrix) revealed significant differences in the bacterial community compositions at different time points, regardless of the ciprofloxacin concentration, and indicated that the combination of time and ciprofloxacin concentrations impacts bacterial communities in the SML and ULW (r2 = 67%, p = 0.001). Marine bacteria of the Rhodobacterales, including the genera Planktomarina, Lentibacter, and unknown Rhodobacteraceae, persist in the presence of 100 ng/mL ciprofloxacin over time. The abundance of Campylobacterales, particularly Arcobacteraceae, increased over time and with increasing ciprofloxacin concentrations, raising concerns about the development and spread of potential antibiotic-resistant pathogens in the SML and ULW. Ninety-seven bacterial strains (42 marine, 55 non-marine) belonging to 14 genera were also enriched and isolated in the presence of 100 ng/mL ciprofloxacin. Further antibiotic susceptibility tests on enriched marine bacteria revealed widespread resistance to ciprofloxacin and other antibiotics found in environmental samples. Our study, therefore, suggests that more efforts are needed to safeguard the integrity of coastal environments and to mitigate the spread of antibiotic-resistant bacteria in the ecosystem.